2016
DOI: 10.1016/j.combustflame.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies characterizing the burning dynamics of wildland fuels

Abstract: International audienceA method to accurately understand the processes controlling the burning behavior of porous wildland fuels is presented using numerical simulations and laboratory experiments. A multiphase approach has been implemented in OpenFOAM, which is based on the FireFOAM solver for large eddy simulations (LES). Conservation equations are averaged in a control volume containing a gas and a solid phase. Drying, pyrolysis, and char oxidation are described by interaction between the two phases. Numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 64 publications
(114 reference statements)
1
37
0
1
Order By: Relevance
“…For example, in some cases, the solid behavior model needs to adapt to the changing thickness of the solid phase, charring process, internal convective heat transfers between the solid/gas phases, and variation of porosity and permeability of the solid phase. Consequently, numerous input parameters are required for conducting a fire simulation with solid material response included . This need for a wide range of input data poses a great challenge for fire modeling, especially, in obtaining accurate input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some cases, the solid behavior model needs to adapt to the changing thickness of the solid phase, charring process, internal convective heat transfers between the solid/gas phases, and variation of porosity and permeability of the solid phase. Consequently, numerous input parameters are required for conducting a fire simulation with solid material response included . This need for a wide range of input data poses a great challenge for fire modeling, especially, in obtaining accurate input parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion behaviors of porous fuels has been investigated for many years, and considerable achievements have been comprehensively applied to understand the development of wildland forest fires. Pine needles [32,33] and shredded papers [23,34] are commonly-used materials to investigate the flame spread of porous fuel. Among all the examinations, there seems to be a consensus that the increasing bulk density will impose restriction on the burning intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters that are used in the numerical simulations are summarised in Table 1 (El Houssami 2016;El Houssami et al 2016).…”
Section: Sub-models and Parametersmentioning
confidence: 99%
“…Indeed, as pointed out by Pickett et al (2010) and McAllister et al (2012), large temperature gradients are observed within fuel particles, with a plateau at ,200-3008C for the particle surface temperature and a plateau at ,1408C for the core temperature, during evaporation (Pickett et al 2010). This behaviour, specific to living fuel, cannot be accounted for using a classical multiphase formulation as in Grishin (1997), Larini et al (1998), Morvan and Dupuy (2001), Séro-Guillaume and Margerit (2002), Mell et al (2009) andEl Houssami et al (2016), because the thermal equilibrium assumption (between the solid and the liquid comprising the fuel particles) and the classical degradation models lead to a plateau at 1008C for the particle temperature. Moreover, the work of Mell et al (2009) does not show comparison between experimental results and numerical simulations for a fuel moisture content (FMC) value higher than 49%, suggesting that this model requires further investigation for high FMC.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation